2022
DOI: 10.1007/s42535-022-00525-w
|View full text |Cite
|
Sign up to set email alerts
|

In-silico docking studies of selected phytochemicals against papain like protease of SARS-Cov-2

Abstract: The SARS-Cov-2 virus, which is evolving continuously and causing adverse effects throughout the world, needs an effective drug molecule for its treatment. There are several receptors of SARS Cov-2 which are targeted for its inhibition by many lead molecules both in-vitro and in-vivo. Papain like Protease (PLpro) is one of the two SARS-Cov-2 proteases that can be used as a drug target for SARS Cov-2. It is a coronavirus enzyme that plays a role in the cleavage and maturation of viral polyproteins, assembly of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…Considering the certainty of the target position, the simulation was conducted with NFKIBA as the In MD simulations, RMSD measures the average deviation or fluctuations in atomic positions in a molecular system from their initial positions, providing insight into the stability of a target protein-ligand complex. Generally, it is considered that once the RMSD value stabilizes and the fluctuation range is less than 0.2 nm, the system can be deemed stable [48]. It can be observed that, for MAPK1, Involucratin and Luteolin reach equilibrium after about 13 ns, with smaller fluctuations than the protein's original ligand 38Z.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…Considering the certainty of the target position, the simulation was conducted with NFKIBA as the In MD simulations, RMSD measures the average deviation or fluctuations in atomic positions in a molecular system from their initial positions, providing insight into the stability of a target protein-ligand complex. Generally, it is considered that once the RMSD value stabilizes and the fluctuation range is less than 0.2 nm, the system can be deemed stable [48]. It can be observed that, for MAPK1, Involucratin and Luteolin reach equilibrium after about 13 ns, with smaller fluctuations than the protein's original ligand 38Z.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%